2003
DOI: 10.1034/j.1600-6143.2003.00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalized Nephrolithiasis after Renal Transplantation in the United States

Abstract: The national incidence of and risk factors for hospitalized nephrolithiasis (NEP) in renal transplant (RT) recipients has not been reported. We conducted a historical cohort study of 42 096 RT recipients in the United States Renal Data System between 1 July 1994 and 30 June 1998. The 1-year incidence of NEP (ICD-9 codes 592.x) after RT in 1997 was compared to the rate of NEP in the general population using the National Hospital Discharge Survey. Associations with time to hospitalizations for a primary diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1
15

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 17 publications
0
20
1
15
Order By: Relevance
“…In addition, UTI were rare and the authors suggested that LUTS and BPH were not clinically significant risk factors for UTI (16). However, the unique susceptibility of the transplanted kidney (denervation, reflux with abnormal ureteral valves, immunosuppression) may influence this situation similarly to posttransplant nephrolithiasis (24). Although we have demonstrated an independent association of BPH and AUR, UTI, and allograft loss, we cannot comment on the specific mechanism of graft loss.…”
Section: Limitationsmentioning
confidence: 66%
“…In addition, UTI were rare and the authors suggested that LUTS and BPH were not clinically significant risk factors for UTI (16). However, the unique susceptibility of the transplanted kidney (denervation, reflux with abnormal ureteral valves, immunosuppression) may influence this situation similarly to posttransplant nephrolithiasis (24). Although we have demonstrated an independent association of BPH and AUR, UTI, and allograft loss, we cannot comment on the specific mechanism of graft loss.…”
Section: Limitationsmentioning
confidence: 66%
“…Elle donne d'excellents résultats même si dans certains cas la néphrostomie est nécessaire pour éviter l'obstruction urétérale par les fragments lithiasiques [8]. La néphrolithotomie percutanée peut aussi être pratiquée [10,11]. L'urétéroscopie a également été utilisée [12,13].…”
Section: Discussionunclassified
“…19,20 A metabolic change in the serum and urine of the renal transplant recipient may be a favoring factor for stone development. Hyperparathyroidism, lower citraturia, 9 higher oxaluria, 21 excessive alkaline urine pH, 19 and cyclosporine-induced hyperuricosuria 22 are contributing factors to different types of stone development, namely, calcium oxalate, calcium phosphate, and uric acid stones.…”
Section: Discussionmentioning
confidence: 99%